ANALYSIS OF STOCK INVESTMENT INTENTIONS AMONG STUDENT INVESTMENT COMMUNITY MEMBERS IN YOGYAKARTA - Bima Rahmat Maulana; Poppy Laksita Rini (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study analyses the factors influencing young people’s stock investment intentions among members of the student investment community in Yogyakarta.Methods: This research is quantitative. Data were collected using a questionnaire and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 4.0 software. The sampling technique used was purposive, with a sample of 152 members of the student investment community in Yogyakarta. The data were analysed for Reliability and Validity tests, discriminant validity tests, R-square tests, Path coefficients tests, and hypothesis tests. Results: The findings indicate that Attitude towards behaviour, Subjective norms, and perceived behaviour have a positive and significant effect on stock investment intentions. The regression analysis yielded an R² of 0.608, indicating 60.8% of the variance explained. Meanwhile, the p-values for the variables Attitude Toward Behaviour, Subjective Norms, and Behavioural Control were 0.000 (<0.05), indicating significant influence on investment intentions.Conclusion: These findings confirm that improving literacy and practical investment training are crucial for building students’ confidence and readiness to invest in the capital market. Therefore, universities and the investment community recommend developing investment training programs, stock market simulations, and practice-based financial education.Further research is recommended to include variables such as financial confidence, the influence of digital influencers, and prior investment experience, and to expand the sample across various regions to obtain more representative results. Keywords: Attitude Toward Behaviour, Behavioural Control, Perceived Stock Investment Intention, Subjective Norms